Patients Attitude towards Surgeons Attire in Our Lady of Lourdes Hospital Drogheda - Babak Meshkat; Gary Allan Bass; Melania Matcovici; Zarah Farnes; Claire Buckley; Omar Al Saffar; Peter Gillen (Kerman University of Medical Sciences, 2015)
Background A doctor's competence and professionalism is often judged on the basis of attire. Our Lady of Lourdes (OLOL) is a leading Irish hospital in the implementation of Bare Below the Elbows (BBTE) policy, however surgical attire is not standardised and there is great variability in attire worn on wards. We aimed to evaluate patients attitude towards surgeons attire in OLOL. Methods A prospective survey of adult surgical in-patients was conducted from October 2013 to February 2014. A twelve-question questionnaire was used as data collection tool, using a five point Likert scale to assess patients response to each question. Data were collected on patient demographics, patients level of trust and confidence based on different surgical attire, and patients perception of different attire worn by surgical teams. Results There were 150 completed surveys during the study period with a male to female ratio of 44% to 56% respectively. The mean patient length of in-hospital stay (LOS) was 4.7 days (range 1-22). The most commonly represented age group was 30-40 years (18%), with a comparable spread among all age groups. The majority of patients found the attire worn by surgeons on the ward to be very appropriate (93%). Majority of responders believed scrubs to be the most appropriate attire for surgeons on wards (39%), followed by shirt and tie with white coat (38%) followed by short sleeved shirt and no tie (18%). Shirt and tie with white coat had a positive effect on patients trust in 63% of responders, a negative effect in 10% and no effect in 26%. Scrubs had a positive effect on patients trust in 63%, negative effect in 11% and no effect in 25%. Short sleeved shirt and no tie had a positive effect in 44%, negative effect in 25% and no effect in 30% of patients. Conclusion Patients in OLOL find attire worn by surgeons to be appropriate. Shirt and tie with white coat or scrubs remains the patient's choice attire for surgeons. Shirt and tie with white coat or scrubs has a more positive effect on trust of patients compared to short sleeved shirt and no tie.